Modul Katalog dan Jasa Pelatihan pada Aplikasi Ramah Pangan Lokal (RAPAL) Berbasis Web di BBP2TP - Aziezah, Nur; Erviyana, Nadia; Sholihah, Walidatush; Novianty, Inna (PUSAT SAINS INDONESIA, 2023)
The Center for the Assessment and Development of Agricultural Technology (BBP2TP) is an institution in the field of the study and development of agricultural technology. BBP2TP already has a web-based application called Local Food Friendly (RAPAL). The purpose of this research is to develop the RAPAL application by adding features to accommodate and disseminate information related to training services as well as search features for a training product or service. The search feature is based on keywords, raw materials, city or district, and type of product. The method used in the development of this application is the prototype method, which consists of communication, a quick plan, quick plan modeling, prototype construction, deployment, and feedback. The result is that the catalog and search features in the RAPAL application can help provide easy access for users to search for information regarding local food products and training services.